Prognostic factors and outcome of Epstein–Barr virus DNAemia in high‐risk recipients of allogeneic stem cell transplantation treated with preemptive rituximab. Issue 3 (13th February 2013) - Patriarca, F.; Medeot, M.; Isola, M.; Battista, M.L.; Sperotto, A.; Pipan, C.; Toffoletti, E.; Dozzo, M.; Michelutti, A.; Gregoraci, G.; Geromin, A.; Cerno, M.; et al.
Abstract Aims and methods This study assessed incidence, predictive factors, and outcome of Epstein–Barr virus (EBV) DNAemia in 100 recipients of allogeneic hematopoietic stem cell transplant. A total of 68 patients received anti‐thymocyte globulin before unrelated grafts. Results Cumulative incidence of high‐load EBV DNAemia defined by levels >10, 000 copies/mL was 14% at 12 months. In multivariate analysis, a CD4+ T‐lymphocyte count >50 μL at day +30 was the only factor significantly associated with a reduced risk of high‐load EBV DNAemia. Thirteen of 16 patients with high viral loads were preemptively treated with rituximab and achieved EBV DNA negativity. Three patients had already developed post‐transplant lymphoproliferative disorder (PTLD) at the time of detection of high EBV DNA loads, and they obtained complete response after rituximab infusions and chemotherapy. Patients with high EBV DNA load had a significantly higher transplant‐related mortality (TRM) compared with patients with negative or low viral load (54% vs. 16%, P = 0.009) and a trend to lower overall survival (55% vs. 29%, P = 0.060). Conclusion We conclude that CD4+ cell count at day +30 is a predictive factor for EBV DNAemia and may help identify patients requiring closer monitoring. Although only 3% of patients progressed to PTLD and were all successfully managed, EBV reactivation was associated with higher TRM, mainly because of infections.